A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
What is the solution to the following equation?
5(2x − 6) + 20 = 10
9
5
3
2
anonymous
 one year ago
What is the solution to the following equation? 5(2x − 6) + 20 = 10 9 5 3 2

This Question is Closed

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0well i guess i should start off by saying i got 2 as my asnwer

pooja195
 one year ago
Best ResponseYou've already chosen the best response.15(2x−6)+20=10 Step 1 5(2x−6)+20=10 Simplify 5(2x−6)+20=10 (5)(2x)+(5)(−6)+20=10(Distribute) 10x+−30+20=10 (10x)+(−30+20)=10(Combine Like Terms) 10x+−10=10 10x−10=10 Step 2: Add 10 to both sides. 10x−10+10=10+10 10x=20 Step 3: Divide both sides by 10. 10x 10 = 20/10 x=2

campbell_st
 one year ago
Best ResponseYou've already chosen the best response.0wow I would have subtracted 20 as the 1st step \[5(2x  6) + 20 20 = 10 20 ~~~so ~~~~ 5(2x 6) = 10\] then divide both sides by 5 \[\frac{5(2x 6)}{5} = \frac{10}{5} ~~~~so~~~~ 2x  6 = 2\] next add 6 to both sides of the equation \[2x  6 + 6 = 2 + 6~~~~or~~~~2x = 4\] now solve for x it saves a few steps
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.